ChemInform Abstract: Dual Gold Catalysis: Synthesis of Polycyclic Compounds via C—H Insertion of Gold Vinylidenes. Issue 13 (March 2015) - Wieteck, Marcel; Tokimizu, Yusuke; Rudolph, Matthias; Rominger, Frank; Ohno, Hiroaki; Fujii, Nobutaka; Hashmi, A. Stephen K.
Abstract This method provides access to complex polycyclic compounds with quaternary carbon centers from non‐conjugated diynes.